Bat algorithm-enabled binary optimization for scattered light focusing. (4th September 2019) - Wang, Zi-Qiang; Zhao, Qian; Yu, Pan-Pan; Yang, Jia-Miao; Li, Yin-Mei; Gong, Lei
Abstract: We introduce a novel global optimization algorithm–bat algorithm (BA) for wavefront shaping to focus light through highly scattered media. Compared with the well-known genetic algorithm, BA-based binary wavefront shaping achieves a higher enhancement with less time in noisy environments, which is validated by simulation and experiment. Using a high-speed digital micromirror device, the BA enables quick formation of single or multiple focal spots through a highly scattering layer. The BA offers a competitive algorithm for wavefront shaping in turbid media, which might benefit biomedical imaging in deep tissues.